Vagueness and intuitionistic logic - Rumfitt, I (Oxford University Press, 2020)
This chapter considers the question: should we employ intuitionistic logic, not classical logic, when reasoning with vague concepts? In his commentary on Michael Dummett’s “Wang’s Paradox,” Crispin Wright presents an apparently powerful argument in favour of an affirmative answer to this question. This chapter advocates a less conclusive answer than Wright’s. It is argued that intuitionistic logic may be the strongest logic we are entitled to use in reasoning with any vague predicate, but there may also be common and central families of vague term where we are entitled to use classical logic.